"Think sustainable, act local" – a stakeholder-filter-model for translating SDGs into sustainability initiatives with local impact. Issue 6 (10th June 2019) - Raub, Steffen P.; Martin-Rios, Carlos
Abstract : Purpose: The purpose of this paper is to develop and illustrate a comprehensive framework for how hospitality firms can overcome the broad vs narrow dilemma in sustainable management. The authors develop a framework for how to break down the United Nations sustainable development goals (SDGs) into actionable and context-specific subsets and select individual sustainability initiatives with maximum impact. Design/methodology/approach: The framework focuses on sustainable innovation and management in hospitality and the issue-focused stakeholder perspective. The authors develop a theoretical framework for the selection of impactful sustainability initiatives in the hospitality industry. In addition, the paper provides a broad range of concrete examples for how different stakeholders can act as barriers or catalysts for the implementation of sustainability initiatives. Findings: The major contribution of this paper is twofold. First, it recognizes that the solutions to the great sustainability challenges ahead involve the active participation of the hospitality industry in establishing partnerships with stakeholders. Second, it offers an ambitious roadmap for hospitality firms to identify local issues specific to sustainable management actions committed to advancing the social, environmental and economic dimensions of sustainability. Originality/value: The framework has considerable practical implications in that it is centered on helping hospitality firms select an appropriate set of SDGs for their local context and translate them into specific sustainability initiatives that address these goals. The "stakeholder-filter model" methodology is aligned with an approach that is already being used for the development of sustainability initiatives outside the scope of the hospitality industry. As a result, the framework should have substantial practical value for the hospitality industry.